Alternate formation of AlOH from third row diatomic hydrides and oxides - Firth, Rebecca A.; Fortenberry, Ryan C. (Frontiers in Astronomy and Space Sciences, 2024)
One of the most abundant Al-containing molecules detected in the interstellar medium (ISM) is AlOH. Over the past several years, there have been various pathways proposed for the formation of AlOH in the ISM, including reactions between AlO and H2 or H2O. However, these pathways include an energetic barrier from a transition state that likely prevents the reaction from progressing efficiently in the low temperature/low pressure environment of the ISM. Recently, a barrierless pathway for formation of AlOH from AlO and AlH has been proposed for the formation of AlOH. Even so, only one of these species really needs to contain an aluminum atom. To account for this, alternative but related pathways reacting the known interstellar molecule AlO with XH and AlH with XO (X = Mg, Si, P, or S) to form AlOH are explored with high accuracy quantum chemical calculations via CCSD(T)-F12b/cc-pVTZ-F12. Each third row element has at least one pair of reactants that lead to exothermic formation of AlOH. These reactions can go on to form other aluminum oxides and aluminum oxide clusters that may, in part, lead to the formation of interstellar dust grains.